HERETABILITAS DAN NILAI PEMULIAAN DOMBA EKOR GEMUK DI KABUPATEN SITUBONDO - H. Darmawan; N. Supartini (Universitas Tribhuwana Tunggadewi, 2012)
Situbondo district is one of the development zone of fat tail sheep. However, there are still have problems in base information of fat tail sheep genetic potential. Aim of this research are to identify genetic potential of fat tail sheep and determine factors of fat tail sheep genetic potential development at Situbondo district. This research used simple random sampling method. Materials research were 99 of third to fourth months old of fat tail sheep which have weaned based on respondents report and assumed from their experiences. Data analized using unpair t-test and estimation of heritability, breeding value and correlation coefficient. The result showed that genetic potential of fat tail sheep known from breeding value estimation with the value of weaning weight heritability as genetically parameter. The heritability of weaning weight corrected on 100 days of age is 0,1462, and the highest breeding value was sire number 19, which is 15,98 kg and it mean that this value is higher 0,64 kg than the population rate. So, we need completely and continously recorded datas of base information of fat tail sheep ganetic potential in order to evaluate the next development prgramme of fat tail sheep